Factors influencing breast cancer screening among reproductive age women in Lesotho: Analysis of the 2023-24 demographic and health survey using the Andersen Behavioral Model - Mesfin Abebe; Yordanos Sisay Asgedom; Amanuel Yosef Gebrekidan; Tsion Mulat Tebeje (PLoS ONE, 2025)
Background Breast cancer is the leading cause of cancer-related deaths in women globally and a significant public health burden in sub-Saharan Africa, which accounts for approximately 15% of all cancer-related mortality. In sub-Saharan Africa, breast cancer incidences increased by 247% from 1990 to 2019. In Lesotho, breast cancer is the second most common cancer affecting women, a situation worsened by a fragile healthcare system and low screening rates. Despite its high morbidity and mortality, there is limited understanding of the factors influencing breast cancer screening among women of reproductive age. This study aims to identify these factors by utilizing the newly released Lesotho DHS dataset and the Anderson Behavioral Model. Methods This study utilized a cross-sectional design with data from the recent Lesotho Demographic and Health Survey (LDHS), which employed a stratified two-stage sampling method across 400 Enumeration Areas and 9,976 households. This analysis included a weighted sample of 6,413 reproductive-age women (15–49 years) to determine factors of breast cancer screening. The predisposing, enabling, and need factors were examined using the Andersen Behavioral Model. Stata version 16 was used for a multilevel mixed-effects logistic regression model. Results were presented as adjusted odds ratios (AOR) with 95% confidence intervals, and a P-value less than 0.05 was considered statistically significant. Results The prevalence of breast cancer screening among women of reproductive age in Lesotho was 22.20% (95% CI 21.19–23.23). Significant factors included age 25–34 (AOR = 1.54; 95% CI 1.26–1.88), age 35–49 (AOR = 2.10; 95% CI 1.71–2.58), healthcare facility visits in the past 12 months (AOR = 1.47; 95% CI 1.26–1.71), health insurance coverage (AOR = 1.86; 95% CI 1.36–2.53), high media exposure (AOR = 1.23; 95% CI 1.01–2.52), contraceptive use (AOR = 1.18; 95% CI 1.03–1.37), and parity: multiparous (AOR = 2.29; 95% CI 1.84–2.85) and grand multiparous (AOR = 1.67; 95% CI 1.16–2.40). Conclusion This finding that 22.2% of reproductive age women in Lesotho underwent breast cancer screening highlights a pressing gap in preventive health efforts. The Andersen Behavioral Model underscores key determinants that significantly influence breast cancer screening uptake in our study. Significant factors included age, healthcare facility visits, health insurance coverage, media exposure, contraceptive usage, and parity. These findings underscore the need for targeted interventions that address model-based determinants to improve breast cancer screening uptake.